Optimizing the Use of Linaclotide in Patients with Constipation-Predominant Irritable Bowel Syndrome: An Expert Consensus Report - Rey, E (2017)
INTRODUCTION: Irritable bowel syndrome (IBS) is a functional bowel disorder characterized by chronic or recurrent abdominal pain in association with defecation or a change in bowel habits. A predominant disorder of bowel habits, IBS is classified into three main subtypes: constipation-predominant IBS (IBS-C), diarrhea-predominant IBS (IBS-D) and IBS alternating between constipation and diarrhea (IBS-M). Linaclotide is a first-in-class, oral, once-daily guanylate cyclase-C receptor agonist (GC-CA) that is licensed for the symptomatic treatment of moderate-to-severe IBS-C in adults. This review aims to facilitate and optimize clinical practices, establishing common guidelines to monitor patients with IBS-C that are treated with linaclotide. METHODS: A group of experts in functional digestive disorders was convened to review the efficacy and safety of linaclotide and to develop an updated consensus report for the treatment of patients with IBS-C. A search was performed for English, French and Spanish language articles in PubMed. On the basis of the articles identified, an initial document was drafted addressing different issues frequently raised by general practitioners and GI specialists that are related to the prescription, efficacy and safety of linaclotide. This document was then reviewed and modified by the expert panel until a final text was agreed upon and validated. RESULTS: Based on the evidence, the panel addressed the following recommendations: (1) Linaclotide is indicated for the treatment of moderate to severe IBS-C in adults; (2) it is recommended that patients take linaclotide continuously and not sporadically; (3) patients should be warned about the risk of diarrhea and given choices concerning how to deal with this possible side effect; (4) the absence of tachyphylaxis or potential risks implies that linaclotide treatment can be maintained for long periods of time. CONCLUSIONS: This document seeks to lay down a set of recommendations and to identify key issues that may be useful for the clinical management of IBS-C patients treated with linaclotide.